First-in-Human Experience With the Gore Balloon-Expandable Covered Endoprosthesis in Iliac Artery Occlusive Disease. (February 2017) - Holden, Andrew; Merrilees, Stephen; Buckley, Brendan; Connor, Brigid; Colgan, Frances; Hill, Andrew
Purpose: To report the first-in-human iliac artery experience of a new balloon-expandable covered endoprosthesis.Methods: A prospective, single-center pilot study recruited 30 symptomatic patients (mean age 64 years; 18 men) to evaluate the safety and early efficacy of the new Gore balloon-expandable covered endoprosthesis for the treatment of de novo or restenotic common and/or external iliac artery lesions. According to protocol, up to 2 discrete lesions could be treated with a maximum total treated length ≤110 mm. Follow-up included clinical evaluation with duplex ultrasound at 1, 6, and 12 months. Data are presented through 12-month follow-up. The primary safety endpoint was a composite of device- or procedure-related death, myocardial infarction, or amputation in the treated leg within 30 days of the index procedure. Multiple performance outcomes were also evaluated.Results: The primary 30-day safety endpoint was 0%. Per-subject estimates of primary patency, freedom from target lesion revascularization, and freedom from target vessel revascularization were 100% at 1 and 6 months and 96.6% at 12 months. Estimates of assisted primary and secondary patency were both 100% at 12 months. Freedom from major adverse events at 12 months was 100%. Most patients experienced improvements in Rutherford category, ankle-brachial index, and functional status that were sustained to 12 months.Conclusion: This positive first-in-human experience with the Gore balloon-expandable covered endoprosthesis suggests this device will have an important role in the management of aortoiliac occlusive disease.